Pediatric aero-digestive foreign bodies in the emergency setup: an otorhinolaryngologist’s perspective - Goswami, Abhilasha; Borah, Hironya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The objective of the study was to investigate cases of foreign bodies in the aero-digestive tract among the paediatric population. Methods: This study was carried out under the aegis of the department of otorhinolaryngology over a one-year period, from April 2019 to March 2020. A total of 82 paediatric patients presented to the emergency department with aero-digestive foreign body, where opinion of the otorhinolaryngologist was sought. All the patients were initially stabilised and assessed clinically. Detailed history was obtained, thorough clinical evaluation done and necessary investigations including radiological tests were performed. After ascertaining the nature and location of the foreign body, prompt removal of the same was done in all the patients under general anaesthesia. Results: A total of 82 children presented to the emergency with history of inhalation/ingestion of foreign body or suspicion of such, and requiring otorhinolaryngological intervention. There were 55 boys and 27 girls, with 74 cases of ingestion and 8 cases of aspiration of foreign body. The most common foreign body ingested was coin and the most common foreign body aspirated was small button battery. Conclusions: Foreign bodies in the aero-digestive tract are a common problem encountered by the otorhinolaryngologist in the emergency setup. It constitutes a health hazard in all age groups, but more so among the paediatric population, requiring effective management and immediate intervention. Careful clinical and radiological evaluation followed by prompt removal of the aero-digestive foreign body is essential to reduce the morbidity and mortality. Prevention and public education are the most vital and ideal management for this serious problem.